MODELING OF TROLLEYBUS TRANSPORT SUPPLY SYSTEM (Perner's Contacts, 2012)
The article demonstrates simulation of trolleybus transport supply system using the Monte Carlo statistical modeling. Verification of this model was implemented by com-parison with the results of measure currents and voltages in Gdynia trolleybus network. In article is presented the case study of using Monthe Carlo methods for analysis of increasing energy recovering in trolleybus transport by installing supercapacitors stations or reconfiguration of supply system topology in case of trolleybus network in Gdynia city.
Keywords: Trolleybus, Electric Traction Power Supply, Monte Carlo methods